2014
DOI: 10.1111/ajco.12322
|View full text |Cite
|
Sign up to set email alerts
|

Spindle cell metaplastic carcinoma of breast: A clinicopathological and immunohistochemical analysis

Abstract: Based on this series, SpCMC is a rare variant of metaplastic breast carcinoma with the distinct histopathological and immunohistochemical features. The biological behaviors of SpCMC, like axillary lymph node status, were quite different from that of IDC, suggesting that it may act as an independent pathologic subtype. Immunohistochemical analysis of a panel of epithelial and myoepithelial markers could contribute to the pathologic diagnosis of SpCMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Focal squamous differentiation may or may not be identified. 3,14 The differential diagnosis of spindle cell carcinoma is similar to that of fibromatosis-like metaplastic carcinoma and includes phyllodes tumor, and primary or metastatic sarcoma. 15 When present, a carcinomatous component, including invasive ductal carcinoma or ductal carcinoma in situ, is extremely useful in this differential diagnosis.…”
Section: Spindle Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Focal squamous differentiation may or may not be identified. 3,14 The differential diagnosis of spindle cell carcinoma is similar to that of fibromatosis-like metaplastic carcinoma and includes phyllodes tumor, and primary or metastatic sarcoma. 15 When present, a carcinomatous component, including invasive ductal carcinoma or ductal carcinoma in situ, is extremely useful in this differential diagnosis.…”
Section: Spindle Cell Carcinomamentioning
confidence: 99%
“…3,12 While the cell of origin of metaplastic carcinoma remains unknown, some investigators have argued that this particular variant may originate from myoepithelial cells, as spindle cell carcinomas are frequently positive for at least 1 myoepithelial marker such as p63, smooth muscle actin, and CD10. 14,16 Carcinoma With Mesenchymal Differentiation These aggressive tumors are composed of an admixture of differentiated mesenchymal components, including chondroid, osseous, rhabdomyoid, and rarely neuroglial elements. 3,17 This type of metaplastic carcinoma is further subclassified by the WHO into 1 of 3 categories: carcinoma with chondroid differentiation, carcinoma with osseous differentiation, and carcinoma with other types of mesenchymal differentiation.…”
Section: Spindle Cell Carcinomamentioning
confidence: 99%
“…For the spindle cell carcinoma variant, in addition to the presence of atypical spindle cell proliferation or proliferation of spindle cells, and areas of focal necrosis, a concurrent invasive ductal carcinoma or in situ component is commonly found to be diagnostic. Common myoepithelial markers such as p63, smooth muscle actin (SMA), C10, as well as calponin, may be diagnostic (1,2,42,43). Subtypes of mesenchymal differentiation, are often described as larger tumours (2,44).…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy reveals a morphology that consists predominantly of sheets of spindle cells (often >80%), with the tumor exhibiting biological behavior resembling that of a sarcoma. Despite the predominance of spindle cells, Zhu et al demonstrated that invasive ductal carcinoma (IDC) and ductal carcinoma in-situ (DCIS) components were visualized in 47% of the spindle cell tissue biopsies sampled from a cohort of 19 patients [ 2 ]. In congruence with the existing data [ 3 ], as well as our present case report, their findings further showed that although immunohistochemical staining in spindle cell carcinoma rarely reveals a hormone receptor-positive disease, a combination of myoepithelial and epithelial markers are frequently observed.…”
Section: Discussionmentioning
confidence: 99%